DYNAMICS OF DISPUTE RESOLUTION IN VILLAGE HEAD ELECTION TASIK SERAI BARAT SUB-DISTRICT TALANG MUANDAU DISTRICT BENGKALIS PERIOD 2017-2023 - Hutabalian, Raja Hizkia; Pane, Rico Purnawandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research is motivated by the village head election which was held simultaneously for the first time in Tasik Serai Barat Village, Talang Muandau District, Bengkalis Regency. The Village Head Election held in Tasik Serai Barat Village aims to elect the village head for the 2017-2023 term. In its implementation, it was found that things were not in accordance with the village head election process conducted for the first time by Tasik Serai Barat Village in 2017. Namely, the re-election of votes caused by objections from three candidates for the temporary village head has been determined by the winning committee in the village head election in Tasik Serai Barat Village. This study aims to determine the causal factors and dispute resolution of the village head election in Tasik Serai Barat village, Talang Muandau sub-district, Bengkalis Regency for the 2017- 2023 period. The research uses a qualitative approach with descriptive methods. The types of data are primary data and secondary data, primary data obtained directly from informants. While secondary data is supporting data or strengthening primary data. Data collection techniques are carried out by means of interviews and documentation. This research uses the theory of horizontal pluralism and vertical pluralism from Ramlan Surbakti, (2010), andthe theory of dispute resolution from Kartikasari SN. (2001). The results of this study indicate that the causes of the Village Head election dispute in Tasik Serai Barat Village are ethnic differences and the distribution of power, theresolution of the village head election dispute in Tasik Serai Barat Village is not well implemented and has not shown the existence of a settlement process that has been regulated in Bengkalis Regency Regional Regulation Number 9 of 2016 concerning Amendments to Bengkalis Regency Regional Regulation Number 7 of 2015 article 50 paragraph (3). Keywords: Dispute Resolution, Village Head Election, Law